EFEKTIVITAS PELATIHAN PENCEGAHAN KEKERASAN SEKSUAL DAN BULLYING DI MAS ULUL ALBAB KOTA TERNATE - Suparman, Suparman; Hamid, Hasan; Haerullah, Ade (Jurnal Abdi Insani, 2024)
Sexual violence and bullying are serious issues that can negatively impact the physical, psychological, and social development of adolescents. This study aimed to evaluate the effectiveness of a training program on the prevention of sexual violence and bullying at MAS Ulul Albab Islamic Boarding School in Ternate City. The training program consisted of three stages: socialization, training, and a declaration and signing of an integrity pact against sexual violence and bullying. The participants were 39 female students from the boarding school. The effectiveness of the program was assessed using indicators such as participants' understanding of the training material, practical skills, attitudes towards prevention, assessment of the training implementation, satisfaction with the facilitators, and participant involvement. Data were collected through tests, questionnaires, observations, and interviews, and analyzed descriptively using simple statistics. The results showed that the training program was highly successful and effective, with an average score of 84.4 out of 100 across all indicators. Participants demonstrated a high level of understanding (87.2), positive attitudes (82.2), and practical skills (80.9) related to the prevention of sexual violence and bullying. They also expressed high satisfaction with the training implementation (82.9) and the facilitators (86.3). The program's success was attributed to the facilitators' experience and the community-based approach, which is suitable for addressing individual-level cases. This study highlights the importance of such training programs in creating a safe and conducive learning environment in Islamic boarding schools and other educational institutions.